Synthesis and Characterization of 2-bromo-4,5-dimethoxybenzaldehyde Compound from Veratraldehyde and KBrO3 In Situ - Nafillah, Khoirotun (Proceeding International Conference on Religion, Science and Education, 2024)
Bromination is an addition reaction of bromo groups in alkene double bounds like benzaldehyde derivatives. Bromination reaction has an important role in the industrial chemistry because of the multifunctionality of organobromide products in various syntheses. However, the use of bromine molecules can be toxic and reactive. An alternative bromination procedure is needed by avoiding directly bromine through an oxidizing agents such as KBrO3. This research aims to carry out synthesis, characterization and scale up study of the compound 2-bromo-4,5-dimethoxybenzaldehyde from veratraldehyde basic material use KBrO3 as a source of in situ bromine. The bromination mechanism in this study used electrophilic aromatic substitution in acidic conditions to produce the gray-white 2-bromo-4,5-dimethoxybenzaldehyde compound with a melting point of 142-144 °C. Scale up study on the compound 2-bromo-4,5-dimethoxybenzaldehyde showed that mass variations on the compound veratraldehyde, namely 0.5; 1.0; 2.0; and 3.0 grams with successive yields of 21.63; 82.03; 69.38; and 69.84%. The synthesis results were characterized using TLC, FTIR, and GC-MS. The FTIR spectrum showed the vibration of the C-Br, C=O, C=C aromatic and C-O ether functional groups. The typical absorption of C-Br shows absorption at a wave number of 1018 cm-1. The mass spectrum showed a molecular ion (M+) with m/z 244 which corresponds to the target molecule.